Wave energy for Australia's National Electricity Market. (September 2015) - Behrens, Sam; Hayward, Jennifer A.; Woodman, Stuart C.; Hemer, Mark A.; Ayre, Melanie
Abstract: This paper examines the opportunities for the renewable resource of wave energy in Australia's National Electricity Market (NEM). Using 9 years of hourly wave resource data and a typical terminator wave energy converter performance curve, hourly electricity generation profiles and normalised annual wave energy capacity factors were calculated in spatially distributed "polygons" of the NEM. A conservative wave farm design with 3.35 wave energy converters per km, and environmental, marine park and general exclusion zone constraints, has been assumed. The polygon spanning western Victoria has the greatest capacity factor of 0.44. Integrating the hourly electricity generation data revealed that polygons in Tasmania can generate the most electricity, equal to 44.4 TWh/yr. Total generation over all NEM polygons was calculated to be 275 TWh/yr. This exceeds Australia's total electricity generation of 255 TWh for the 2011−2012 financial year. Therefore, wave energy could potentially provide sufficient electricity generation to meet demand in the NEM region. Highlights: Assessed opportunity in Australian National Electricity Market (NEM) for wave farms. Total generation using wave energy was calculated to be 275 TWh/yr. Wave farms could provide significant electricity generation to the Australia's NEM.